Active transport of manganese in isolated membrane vesicles of Bacillus subtilis. - Bhattacharyya, P (1975)
Membrane vesicles isolated from cells of bacillus subtilis W23 accumulate manganese in the presence of an energy source. The artificial electron donor system ascorbate and phenazine methosulfate or reduced nicotinamide adenine dinucleotide and phenazine methosulfate can supply the energy for the uptake. D-Lactate in the presence or absence of phenazine methosulfate would not support manganese accumulation. Anaerobiosis, cyanide, m-chlorophenyl carbonylcyanide hydrozone, valinomycin, gramicidin, and p-hydroxy-mercuribenzoate inhibit the uptake. The inhibition by p-hydroxymercuribenzoate is prevented by excess dithiothreitol. Potassium fluoride or sodium arsenate has no effect on the uptake. The manganese transport system in the B. subtilis vesicles exhibits Michaelis-Menten kinetics with a Km of 13 muM and a Vmax of 1.7 nmol/min per mg (dry weight) of membranes. The uptake of manganese is specific and is not inhibited by 0.1 mM CaCL2 or Mgcl2.